Produção e caracterização de proteínas recombinantes de Mycoplasma hyopneumoniae com potencial para uso em imunodiagnóstico e vacinação - Simionatto, Simone (2008)
Mycoplasma hyopneumoniae is the etiological agent of porcine enzootic pneumonia (EP), a respiratory disease responsible for significant economic losses. Commercial vaccines are widely used in the control of this disease, however, they provide only partial protection. Besides, their preparation is expensive because of fastidiously growth of M. hyopneumoniae in vitro. Therefore, the development of alternatives for EP prophylaxis is important for improving health conditions of pigs. Recombinant DNA technology can be used to overcome problems with conventional vaccines. Nevertheless, because of the use of TGA and not TGG to code for tryptophan, translation of mycoplasmal genes terminates prematurely when cloned in other bacteria, such as Escherichia coli. Because of this, the number of antigenic proteins characterized to date in vaccine formulations or immunodiagnostic tests is still restricted. In this work, 63 genetic fragments were selected, which correspond to 48 sequences coding (CDS) of M. hyopneumoniae. First, an overlap extension-PCR method for site-directed mutagenesis of M. hyopneumoniae genes was standardized, aiming at substituting TGA codon by TGG. With this improved method, site-directed mutagenesis was successfully achieved in 14 M. hyopneumoniae genes. Other selected genes were amplified by PCR and cloned into Champion pET200D/TOPO®. A total of 59 genetic fragments were efficiently cloned. From these, 49 had their proteins expressed in E. coli and 35 were purified by affinity chromatography using Ni- Sepharose columns (HisTrap ). Immunogenic and antigenic properties of these proteins were analyzed. For this, the proteins were tested against sera from hyperimmune and from convalescent pigs through ELISA (enzyme-linked immunosorbent assay) and Western blot. Nineteen recombinant proteins were specifically recognized by convalescent pig sera indicates they are expressed during infection. Immune humoral response against recombinant proteins was evaluated in BALB/c mice by ELISA. The results showed that antigens induce variable levels of antibodies, which allows inferring the immunogenicity of each antigen. Sera from inoculated mice with twenty recombinant proteins were able to recognize the native protein by ELISA. This study allowed identifying and characterizing new immunogenic proteins according to their potential for use in diagnostic tests and/or vaccine. These data represent an important contribution for the development of more efficient serological tests and a subunit vaccine for controlling M. hyopneumoniae infections in pigs.